TECHNO-ECONOMIC ANALYSIS OF A COMMUNITY-OWNED RENEWABLE ENERGY COOPERATIVE BASED ON A WAQF (ISLAMIC ENDOWMENT) MODEL - Siti Mariam; Ayesha Begum; Pieter Hendriks (Yayasan Adra Karima Hubbi, 2025)
The global energy transition requires novel, equitable financing models for decentralized, community-owned renewable energy (CORE) systems, as high-cost conventional capital often renders essential infrastructure projects financially unviable in developing regions. This study aims to develop and validate a bespoke Techno-Economic Model (TEM) that quantifies the structural benefits of integrating a CORE cooperative with the perpetual, non-profit Waqf (Islamic Endowment) financing mechanism. A quantitative approach utilized the TEM to optimize a 25-year microgrid project lifespan, comparing a Waqf-funded scenario (zero cost of capital, 30% mandatory asset preservation fund) against a Conventional Debt Benchmark (CDB) with an 8.5% interest rate. The optimized 250 kWp PV/500 kWh BESS Waqf-CORE system achieved a Levelized Cost of Energy (LCOE) of 0.081/kWh, which is 35.2% lower than the CDB’s LCOE of 0.125/kWh. This cost reduction equated to a 1.83 million capital avoidance over the project’s Net Present Cost (NPC). The Waqf model fundamentally eliminates debt-related overheads and ensures perpetual asset maintenance, proving that patient, ethical capital is structurally superior for long-duration public utility infrastructure. This offers a robust, scalable, and self-sustaining blueprint for achieving energy access and climate resilience in Muslim-majority nations and beyond.